Technology for underdeveloped areas an annotated bibliography. - Baranson, Jack (International series of monographs in library and international science, 1967)
Technology for Underdeveloped Areas: An Annotated Bibliography focuses on the functional aspects of technology, including the economic criteria of choice, the institutional requisite for transmittal, and the cultural constraints upon proficiency. This book discusses the relevant concepts, provides specific examples of products and systems required by developing economies, and indicates organizational approaches to adapting advantageous technology.